2000
DOI: 10.1177/154193120004403354
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Workload while Driving and Talking on a Cellular Phone or to a Passenger

Abstract: Twelve adults experienced in using cellular telephones participated in an investigation of driving and performing a communication task. They navigated a closed serpentine driving course, requiring constant driving activity. Their communication task was responding to a verbal cognitive test battery administered by the passenger or via cellular telephone. The test battery consisted of sentence remembering with read-back and verbal puzzle solving. Baseline treatments were navigating the course without communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Also, to counter overload from using the cell phone while driving, drivers often increase their safety margins by increasing headways to vehicles ahead (Brookhuis et al, 1991;Ishida and Matsuura, 2001), or by reducing their speed (Ishida and Matsuura, 2001;Waugh et al, 2000). In addition to pacing or modifying the driving, drivers can also pace the phone conversation (Waugh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Also, to counter overload from using the cell phone while driving, drivers often increase their safety margins by increasing headways to vehicles ahead (Brookhuis et al, 1991;Ishida and Matsuura, 2001), or by reducing their speed (Ishida and Matsuura, 2001;Waugh et al, 2000). In addition to pacing or modifying the driving, drivers can also pace the phone conversation (Waugh et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The demands associated with the verbal and cognitive requirements of conversation via wireless telephone affect a wide variety of skills and abilities critical to safe driving, such as judging whether one's vehicle can fit through a certain gap (Brown, Tickner, & Simmonds, 1969) or adapting to changes in the velocity of a leading vehicle (Brookhuis, de Vries, & de Waard, 1991). Research examining real and simulated driving performance also found that concurrent verbal tasks result in more glances away from the road (Jenness, et al, 2002), increased reaction time to braking events (Irwin, Fitzgerald, & Berg, 2000), increased subjective mental workload (Haigney, Taylor, & Westerman, 2000;Waugh, et al, 2000), and a smaller window of gaze, with glances more concentrated towards the center of the field of vision and reduced glances to side mirrors and speedometer (Recarte & Nunes, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The battery included solving a puzzle, repeating a sentence, and talking on a specific topic (27). The participants were asked to answer the prerecorded questions that were played section by section using a speaker located on the left side of the participants to simulate a phone conversation.…”
Section: Simulated Hands-free Phone Conversations (Hpfc)mentioning
confidence: 99%